Potential Use of Saraca Asoca in the Management of Artavadushti w.s.r. to Menstrual Disorders in Modern Era - Sushma,; L.P. Yadava, (International Journal of Ayurveda and Pharma Research, 2021)
Progress of a family depends on health of women in the family because she is the only creature who has amazing power of creation. A woman suffers from various menstrual disorders (Artavadushti) in her life span. Ashoka (Saraca indica or Saraca asoca (Roxb.), belonging to the family Caesalpinioideae, is one of the most important herb extensively used in bleeding disorders in women throughout her active reproductive period. Ashoka means no grief in Sanskrit language. So it is also called as “friend of women” because it has reputation of its bark for retaining a woman healthy and youthful. Chemically, it contains glycosides, flavonoids, tannins and saponins. Its actions are spasmogenic, uterotonic, oxytocic, antibacterial, antit-umour, anti-implantations, anti-progestational and anti-estrogenic to fight against menorrhagia, leucorrhoea and anticancer. In view of these properties and also its Rasa, Guna, Veerya, Vipaka it can be used in the treatment of bleeding gynaecological diseases.